117k views
1 vote
How do i distribute this into an equivalent expression? -12(-2+4)

2 Answers

5 votes

Answer:

24-48=-24

Explanation:

-12x-2=24

((since two negative numbers multiplied equals a positive))

-12x4=-48

((since a negative times a positive equals a negative))

Soooooooo

24-48=-24

Hope this helps!

User TTZ
by
5.3k points
4 votes

Explanation:

-12 x -2

-12 x 4

=24+-48

Final answer is -24

User Krxldfx
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.